2022
DOI: 10.1016/j.envres.2021.111970
|View full text |Cite
|
Sign up to set email alerts
|

Satellite data and machine learning reveal a significant correlation between NO2 and COVID-19 mortality

Abstract: The Coronavirus disease 2019 (COVID-19) pandemic has officially spread all over the world since the beginning of 2020. Although huge efforts are addressed by scientists to shed light over the several questions raised by the novel SARS-CoV-2 virus, many aspects need to be clarified, yet. In particular, several studies have pointed out significant variations between countries in per-capita mortality. In this work, we investigated the association between COVID-19 mortality with climate variables and air pollution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
1
11
0
1
Order By: Relevance
“…From the review summarized above, we can conclude the health hazard of air pollutions were diverse. From the recent findings of Amoroso et al ( 4 ), Cazzolla Gatti et al ( 6 ), Hadei et al ( 7 ), Sethi et al ( 12 ), air pollution brings impacts on human health as well as to the Covid-19 related hazards. The studies showed that the air pollution affected the mortality and fatalities of the Covid-19 patients, as well as the infected rate or morbidity of Covid-19 with the presence of pollutants in the air.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…From the review summarized above, we can conclude the health hazard of air pollutions were diverse. From the recent findings of Amoroso et al ( 4 ), Cazzolla Gatti et al ( 6 ), Hadei et al ( 7 ), Sethi et al ( 12 ), air pollution brings impacts on human health as well as to the Covid-19 related hazards. The studies showed that the air pollution affected the mortality and fatalities of the Covid-19 patients, as well as the infected rate or morbidity of Covid-19 with the presence of pollutants in the air.…”
Section: Resultsmentioning
confidence: 98%
“…The majority of the studies conducted had analyzed the impact of particulate matter (PM 2.5 , PM 10 , PM <2.5 ) on human health ( 3 , 5 18 , 28 ). Pollution markers such as ozone (O 3 ), carbon monoxide (CO), nitrogen dioxide (NO 2 ) and sulfur dioxide (SO 2 ) are among other important contaminants that were studied by ( 2 4 , 6 , 7 , 10 15 ). Chemicals such as nitrogen oxides (NO x ) also played crucial roles in causing adverse health effects in humans, for instance, cardiorespiratory diseases and cancers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… De Rijcke et al, 2021 , Department for Environment Food & Rural Affairs (DEFRA) 2020 , Dzisi and Dei, 2020 , Eisen et al, 2007 , Epstein et al, 2006 , European Union (EU) 2020 , Food and Agriculture Organization (FAO) 2020 , Ferrarin et al, 2021 , García de Abajo et al, 2020 , Gola et al, 2021 , Greenbaum, 2018 , Grignani et al, 2020 , Gude and Muire, 2021 , Haddad et al, 2015 , Hirota, 2020 , Al-Gheethi et al, 2020 , Kasloff et al, 2021 , Katelaris et al, 2021 , Lacina and Goold, 2015 , Lacina and Hegedüs, 2020 , Langone et al, 2021 , Almilaji, 2021 , López-Feldman et al, 2021 , Maal-Bared et al, 2021 , Magazzino et al, 2020 , Mallapaty, 2021 , Marquès and Domingo, 2021 , Marquès et al, 2021 , Altamimi and Ahmed, 2020 , Martins et al, 2020 , Mauter and Fiske, 2020 , Medema et al, 2020 , Megahed and Ghoneim, 2021 , Missoni et al, 2020 , Amoroso et al, 2022 , Muraina, 2020 , Nardell, 2021 , Occupational Safety and Health Administration (OSHA) 2021 , Petrosino et al, 2021 , De Angelis et al, 2021 , Razzini et al, 2020 , Ren and Chen, 2021 , Arslan et al, 2020 , Rubin, 2020 , Sala-Comorera et al, 2021b , Sangkham et al, 2021 , Smith et al, 2014 , Staddon et al, 2020 , Suzán et al, 2009 , Achak et al, 2021 , Turner et al, 2020 , United Nations (UN) 2020 , Aygün and Tüfekçi, 2020 ,…”
Section: Uncited Referencesmentioning
confidence: 99%
“…O objetivo de [Amoroso et al 2021] foi avaliar a existência de associac ¸ão estatística entre a exposic ¸ão a poluentes e a mortalidade por COVID-19. Foram coletados três tipos distintos de dados, as concentrac ¸ões de poluentes recuperadas dos dados S-5p (monitoramento da atmosfera da Terra, da qualidade do ar, do clima e da camada de ozônio), dados climáticos do ERA5(cobertura completa das variáveis climáticas em toda a Europa) e os dados que caracterizam o contexto socioeconômico, incluindo taxas de mortalidade, coletados em vários repositórios online.…”
Section: Trabalhos Relacionadosunclassified